REPUTATION AND TRUST IN SHARING ECONOMY PLATFORMS: THE CASE OF TRAITY - MARTINEZ-POLO, Josep M; MARTÍNEZ-SÁNCHEZ, Jesús (Annals of Spiru Haret University. Economic Series, 2018)
The concept of reputation is assiduously used in various fields such as communication, public relations, advertising, marketing and management. The convergence between the rise of new technologies linked to corporate communication has favoured the birth of what has been called online reputation. Thus, unprecedented behaviours have been generated that are establishing new social forms and even some authors speak of a new economy of reputation where society would be highly connected through networks and organizations that would operate in an ecosystem of permanent influence from the interest groups. With this premise, Traity arises the project that we analyzed in our research and that raises a reputational score that takes advantage of the fingerprint information to reproduce online trust as we understand it in the physical world, but without trying to reduce its people into a percentage, a number or some stars.